2022
DOI: 10.1038/s41598-022-15706-5
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial reactive oxygen-forming NADPH oxidase 5 is a possible player in diabetic aortic aneurysm but not atherosclerosis

Abstract: Atherosclerosis and its complications are major causes of cardiovascular morbidity and death. Apart from risk factors such as hypercholesterolemia and inflammation, the causal molecular mechanisms are unknown. One proposed causal mechanism involves elevated levels of reactive oxygen species (ROS). Indeed, early expression of the ROS forming NADPH oxidase type 5 (Nox5) in vascular endothelial cells correlates with atherosclerosis and aortic aneurysm. Here we test the pro-atherogenic Nox5 hypothesis using mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Monocyte Nox is activated by enhanced p22phox expression and p47phox translocation, which is the basis of oxidative stress in T2DM patients [ 15 ]. ROS derived from the Nox subtypes Nox1, Nox2, and Nox4 lead to vascular dysfunction in diabetic retinopathy, and Nox5-derived ROS increase the incidence of abdominal aortic aneurysms in diabetic patients [ 16 , 17 ]. Surprisingly, Nox4 has a protective role in diabetic atherosclerosis [ 18 ].…”
Section: Sources Of Ros Production In Diabetic Vascular Endothelial C...mentioning
confidence: 99%
“…Monocyte Nox is activated by enhanced p22phox expression and p47phox translocation, which is the basis of oxidative stress in T2DM patients [ 15 ]. ROS derived from the Nox subtypes Nox1, Nox2, and Nox4 lead to vascular dysfunction in diabetic retinopathy, and Nox5-derived ROS increase the incidence of abdominal aortic aneurysms in diabetic patients [ 16 , 17 ]. Surprisingly, Nox4 has a protective role in diabetic atherosclerosis [ 18 ].…”
Section: Sources Of Ros Production In Diabetic Vascular Endothelial C...mentioning
confidence: 99%
“…Regarding the precise implication of NOX5 in this process, it has been described that the mRNA and protein levels of NOX5 as well as the calcium-dependent NADPH oxidase activity are significantly increased in the atherosclerotic coronary arteries from patients with coronary artery disease as compared to nonatherosclerotic vessels [ 47 ]. However, in a recent work employing a humanized Nox5 knock-in mice that expressed NOX5 in endothelial cells to test the pro-atherogenic hypothesis, Ho et al [ 50 ] found that the expression of the oxidase per se was insufficient to induce aortic atherosclerotic lesions, even in aged mice and exposed to a high cholesterol atherogenic diet. Moreover, in the same work, the authors demonstrated that the endothelial expression of NOX5 did not aggravate aortic atherosclerosis in the atherosclerosis-prone ApoE −/− mice with and without induction of diabetes [ 50 ].…”
Section: Role Of Nox5 In Physiology and Pathophysiologymentioning
confidence: 99%
“…However, in a recent work employing a humanized Nox5 knock-in mice that expressed NOX5 in endothelial cells to test the pro-atherogenic hypothesis, Ho et al [ 50 ] found that the expression of the oxidase per se was insufficient to induce aortic atherosclerotic lesions, even in aged mice and exposed to a high cholesterol atherogenic diet. Moreover, in the same work, the authors demonstrated that the endothelial expression of NOX5 did not aggravate aortic atherosclerosis in the atherosclerosis-prone ApoE −/− mice with and without induction of diabetes [ 50 ]. Another process related to vascular diseases in which NOX5 appears to be involved is in vascular calcification, the formation of calcium phosphate crystals in the vessel wall that promotes vascular stiffness.…”
Section: Role Of Nox5 In Physiology and Pathophysiologymentioning
confidence: 99%
“…The NOX5 gene is absent from rodent species and this has hampered our understanding of its role in atherosclerosis. A recent study using knock-in mice expressing human NOX5 in endothelial cells showed that NOX5 does not promote atherosclerosis [ 28 ], although deletion of NOX5 in New Zealand White rabbits significantly increased plaque development in the thoracic aorta, suggesting a protective role of NOX5 [ 29 ]. However, the role of NOX5 in human atherosclerosis remains unclear.…”
Section: Sources Of Ros In Atherosclerosismentioning
confidence: 99%